2014
DOI: 10.1007/s11064-014-1384-1
|View full text |Cite
|
Sign up to set email alerts
|

Danhong Injection Attenuates Ischemia/Reperfusion-Induced Brain Damage Which is Associating with Nrf2 Levels In Vivo and In Vitro

Abstract: Danhong injection, a Chinese Materia Medica standardized product extracted from Radix Salviae miltiorrhizae and Flos Carthami tinctorii, is used extensively for the treatment of cerebrovascular diseases such as acutely cerebral infarction in clinic. In this study, we further investigated the mechanisms of Danhong injection on cerebral ischemia/reperfusion (I/R) damage relating to Nrf2/ARE signalling pathway in vivo and in vitro. For in vivo experiment, cerebral I/R injury was induced through middle cerebral ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Activation of Nrf2/ARE and its downstream genes has been shown to protect against organ damage in ischemia/reperfusion injury [44, 45]. However, pathophysiological mechanisms of different conditions, severity, and progression point to differential effects on Nrf2 expression [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Nrf2/ARE and its downstream genes has been shown to protect against organ damage in ischemia/reperfusion injury [44, 45]. However, pathophysiological mechanisms of different conditions, severity, and progression point to differential effects on Nrf2 expression [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase (HO)-1 is a major phase II detoxifying enzyme regulated by Nrf2 (10)(11)(12) that protects the body from ROS damage and is the main mechanism that protects cells against oxidative damage (7,13,14). Previous studies have reported that Nrf2 has an important role in I/R injury of the small intestine and brain (15)(16)(17); however, its role in hepatic I/R injury has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies revealed that DHI increased endothelial-dependent vasorelaxation in vivo and ex vivo in rat aortas via prostacyclin/ cyclooxygenase-2 pathway [11]. DHI could prevent ischemia/reperfusion-induced brain damage through activating Nrf2/ARE signaling pathway [12]. Interestingly, DHI protected rat cardiac myocyte damage induced by overdose arginine vasopressin (AVP) and significantly decreased the injury of both primary rat neuronal cells and rat cardiac myocytes.…”
Section: Introductionmentioning
confidence: 99%